Characterization of Lemon Pepper and Black Ginger Extracts and Macroemulsions as Natural Pain Relievers for Spice Stick Balsam Formulation - Yanti; Celinia Harijono; Bibiana Widiyati Lay (MDPI AG, 2023)
Lemon pepper or andaliman (Zanthoxylum acanthopodium) and black ginger (Kaempferia parviflora) are rich in bioactive compounds that possess antioxidant and anti-inflammatory activities. Our recent study demonstrated that andaliman ethanolic extract also exerted anti-arthritic and anti-inflammatory effects in arthritic mice in vivo. Therefore, natural anti-inflammatory and anti-arthritic compounds for alternative natural pain relievers in balsam formulation are needed. This study aimed to produce and characterize lemon pepper and black ginger extracts and their macroemulsion products, followed by formulation, characterization, and stability of spice stick balsam products containing lemon pepper and black ginger macroemulsions. The extraction yields obtained were 24% w/w for lemon pepper and 59% w/w for black ginger. GC/MS results showed that the lemon pepper extract contained limonene and geraniol compounds, and black ginger extract contained gingerol, shogaol, and tetramethoxyflavone compounds. Spice extracts were successfully made in the form of a stable emulsion. The antioxidant activity in both spice extracts and emulsions was relatively high (>50%). The five stick balsam formulas obtained had a pH of 5, 4.5-4.8 cm spread ability, and 30-50 s of adhesion. The stability of products showed no microbial contamination. Based on the organoleptic results, the stick balsam formula of black ginger and black ginger: lemon pepper (1:3) was the most preferred by the panelists. In conclusion, lemon pepper and black ginger extracts and macroemulsions could be used as natural pain relievers in stick balsam products to promote health protection.